The OECD and the nation-state: an interdependent but ambivalent relationship - Ninni Wahlström; Andreas Nordin (Taylor & Francis Group, 2024)
The aim of this article is to explore the interrelationships between a national government and the Organisation for Economic Co-operation and Development (OECD) in terms of the power and legitimization of education reforms, here based on the reciprocal dependence of the two actors. Although the current case study only analyses the shifting relationships between Sweden and the OECD, the assumption is that the case is quite representative of the ambiguities of power in the relationships between the OECD and its smaller member countries and the Nordic countries in particular. To explore the relationship between the Swedish national government and OECD, we make use of discursive institutionalism as a general framework. For a closer understanding of the standpoints of the OECD and Sweden on different matters and at different times, two explanation logics are used. The discourses we found characterizing the different kinds of relationships over time are a discourse of opposition, a discourse of mentorship and a discourse of subordination. We argue that there are both ideational and institutional reasons affecting the conditions for cooperation on educational policy. Although institutional reasons strengthen the maintenance of the cooperation, ideational reasons both challenge and develop the nature of the collaboration between the OECD and Sweden.